2020
DOI: 10.1101/2020.01.07.897298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome wide association study pinpoints key agronomic QTLs in African riceOryza glaberrima

Abstract: 18Background 19 African rice, Oryza glaberrima, is an invaluable resource for rice cultivation and for the improvement of biotic and 20 abiotic resistance properties. Since its domestication in the inner Niger delta ca. 2500 years BP, African rice has 21 colonized a variety of ecologically and climatically diverse regions. However, little is known about the genetic basis of 22 quantitative traits and adaptive variation of agricultural interest for this species. 23 Results 24Using a reference set of 163 fully r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 79 publications
0
12
1
Order By: Relevance
“…We focused our analysis on two climate variables that were the most pertinent to annual species, i.e., mean temperature of the wettest quarter (bio8) and mean precipitation of the wettest quarter (bio 16), respectively. A GWAS with these climate variables has been performed 106 . Briefly, we first used the impute method from the R package LEA v2.0 101 to fill the gaps in the genotypic matrix in order to achieve greater power.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our analysis on two climate variables that were the most pertinent to annual species, i.e., mean temperature of the wettest quarter (bio8) and mean precipitation of the wettest quarter (bio 16), respectively. A GWAS with these climate variables has been performed 106 . Briefly, we first used the impute method from the R package LEA v2.0 101 to fill the gaps in the genotypic matrix in order to achieve greater power.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, several single nucleotide polymorphisms (SNPs) close to two major resistance genes RYMV1 and RYMV3 were identified. However, the SNPs associated with resistance conferred by RYMV1 and RYMV3 were not found in regions flanking any of the identified partial resistance QTLs indicating differences in genes and pathways of resistance ( Cubry et al, 2020 ) suggesting the complex mechanism of partial resistance to RYMV in rice.…”
Section: Genetic Determinants and Mechanisms Of Quantitative Resistance To Rymvmentioning
confidence: 99%
“…For example, Orjuela et al (2013) reported on the co-localization of QTL1 in a 151-kb interval of the RYMV2 gene, hence this QTL may combine complete and partial resistance. Genome-wide association analysis study (GWAS) involving various accessions of O. glaberrima also revealed considerable relationships between quantitative resistance and two known major resistance genes ( Cubry et al, 2020 ). In the same study, several single nucleotide polymorphisms (SNPs) close to two major resistance genes RYMV1 and RYMV3 were identified.…”
Section: Genetic Determinants and Mechanisms Of Quantitative Resistance To Rymvmentioning
confidence: 99%
See 1 more Smart Citation
“…This panel was further used to identify QTLs associated with flowering time, panicle architecture and resistance to Rice yellow mottle virus, providing insights into the adaptive variation of African rice as compared to Asian rice (Cubry et al, 2020). Due to its adaptation to contrasted environments, we hypothesized that O. glaberrima could also be a source of interesting alleles for improving TE.…”
Section: Introductionmentioning
confidence: 99%